Shop Floor Power: Opportunity and Collectivism in Nurses’ Collective Resignations - Granberg, Magnus (Nordic Journal of Working Life Studies, 2017)
This historical and comparative study attends to the phenomenon of collective resignation by registered nurses in the Swedish health services, with the aim of exploring the existence and utilization of shop floor power. The study uses two kinds of data: incidences of collective resignation since the 1980s are explored using newspaper data; second, two cases of collective resignation are comparatively explored using interview data. First is analyzed how contemporary opportunities to take this form of worker action arose. Then is analyzed how differences between the two cases shed further light on opportunity structures in different contexts of nursing, and on nurses’ ability to organize the resignation threat as a collective act. The study clarifies the existence of nurses’ shop floor power as it relates to opportunity structures, while also pointing to the significance of the extent of collectivism when nurses challenge employers by threatening this kind of industrial action